Disentangling the interplay of positive and negative selection forces that shaped mitochondrial genomes of Gammarus pisinnus and Gammarus lacustris. Issue 1 (8th January 2020) - Sun, Shengming; Wu, Ying; Ge, Xianping; Jakovlić, Ivan; Zhu, Jian; Mahboob, Shahid; Al-Ghanim, Khalid Abdullah; Al-Misned, Fahad; Fu, Hongtuo
Abstract : We hypothesized that the mitogenome of Gammarus lacustris (GL), native to the Qinghai-Tibet Plateau, might exhibit genetic adaptations to the extreme environmental conditions associated with high altitudes (greater than 3000 m). To test this, we also sequenced the mitogenome of Gammarus pisinnus (GP), whose native range is close to the Tibetan plateau, but at a much lower altitude (200–1500 m). The two mitogenomes exhibited conserved mitochondrial architecture, but low identity between genes (55% atp8 to 76.1% cox1 ). Standard (homogeneous) phylogenetic models resolved Gammaridae as paraphyletic, but 'heterogeneous' CAT-GTR model as monophyletic. In indirect support of our working hypothesis, GL, GP and Gammarus fossarum exhibit evidence of episodic diversifying selection within the studied Gammaroidea dataset. The mitogenome of GL generally evolves under a strong purifying selection, whereas GP evolves under directional (especially pronounced in atp8 ) and/or relaxed selection. This is surprising, as GP does not inhabit a unique ecological niche compared to other gammarids. We propose that this rapid evolution of the GP mitogenome may be a reflection of its relatively recent speciation and heightened non-adaptive (putatively metabolic rate-driven) mutational pressures. To test these hypotheses, we urge sequencing mitogenomes of remaining Gammarus species populating the same geographical range as GP.